2010
DOI: 10.1111/j.1365-4632.2010.04529.x
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen vs. non‐tamoxifen treatment for advanced melanoma: a meta‐analysis

Abstract: Although tamoxifen (TAM) is routinely used in advanced melanoma, it is still uncertain whether evidence exists to support this practice. This review assesses the benefits and harms of systemic therapy with TAM vs. without TAM on response and mortality in patients with advanced melanoma. MEDLINE, The Cochrane Database of Systemic Reviews, The Cochrane Central Register of Controlled Trials, EMBASE and LILACS were searched for randomized controlled trials comparing chemotherapy using and not using TAM in any dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 31 publications
(122 reference statements)
0
33
0
Order By: Relevance
“…More recently, in a meta-analysis including nine randomized controlled trials, the inclusion of tamoxifen in systemic chemotherapy improved the overall and the partial response of patients with advanced melanoma, with female patients being more likely to respond (Beguerie et al, 2010). However, the incidence of hematologic toxicity was higher in the tamoxifen group, and there was no improvement in 1-year mortality (Beguerie et al, 2010).…”
Section: The Use Of Tamoxifen In Malignant Melanoma Therapy Is An Unsmentioning
confidence: 94%
“…More recently, in a meta-analysis including nine randomized controlled trials, the inclusion of tamoxifen in systemic chemotherapy improved the overall and the partial response of patients with advanced melanoma, with female patients being more likely to respond (Beguerie et al, 2010). However, the incidence of hematologic toxicity was higher in the tamoxifen group, and there was no improvement in 1-year mortality (Beguerie et al, 2010).…”
Section: The Use Of Tamoxifen In Malignant Melanoma Therapy Is An Unsmentioning
confidence: 94%
“…The effects of chemotherapy with and without tamoxifen for the treatment of aggressive melanoma were compared in different clinical trials. These studies reported that co-treatment with tamoxifen may provide improvements in response rates, although it is often accompanied by increased toxicity and no survival benefit (60, 127131). It has been proposed that this is due to the fact that tamoxifen may decrease cell proliferation when it binds to ERα while it may increase cell proliferation when it binds to ERβ (60).…”
Section: Antitumor Activity Of Erβ In Melanomamentioning
confidence: 99%
“…Tamoxifen monotherapyinmetastaticmelanomahasbeenreportedtoinduce remissions in about 5% of the patients, in some cases after progressionofthediseaseinthefirstmonthsoftherapy [5]. Incombinationwithchemotherapy,tamoxifenfailedtoexert an additional therapeutic effect in most studies [6]. But, to our knowledge, no results are published about tamoxifen maintenancefollowingchemotherapy.…”
mentioning
confidence: 68%